Use of Smart Switch in Electrical System - Johan Pongoh; Jonathan Goniwala; Dhean Reinaldy laudevan Anthe; Marhaban Manabung; Epiko Kogoya (Publikasi Indonesia, 2025)
Switches are essential components in electrical installations, serving to control the flow of electricity by either connecting or disconnecting circuits. While conventional switches are widely used, their effectiveness and efficiency are often limited, particularly in terms of energy conservation and automatic management of electrical devices. This issue creates a demand for innovation in the form of smart switches that can enhance control, safety, and energy efficiency. This study aims to analyze the use of smart switches in electrical systems and their implications for safety and energy efficiency. The method employed involves a literature review and comparative analysis of households, hotels, and high-rise building installations that utilize smart switches. The results indicate that smart switches provide more flexible control over electrical devices, enable automatic disconnection when not needed, enhance electrical safety, and support energy conservation. The implications highlight the importance of adopting smart switches in various electrical installations to improve energy efficiency, safety, and user convenience, while also serving as a reference for the development of modern electrical systems in the future.